Analysis of dispersion behavior of aluminum powder in a 20 L chamber with two symmetric nozzles. Issue 1 (9th September 2019) - Yao, Ning; Wang, Liqiong; Bai, Chunhua; Liu, Nan; Zhang, Bo
Abstract: Although aluminum (Al) powder is a potential fuel that has been widely used in many important fields, Al powders are dangerous because of its flammable and explosive characteristics. From this point of view, the investigation of the explosion characteristics of Al powders is of critical importance. The characteristics of a dust explosion are closely related to the dispersion behavior of the powders. The purpose of this research is to analyze the dispersion behavior of Al powder and the uniformity of dust cloud. The dispersion process of Al powders was studied using a high‐speed camera. Image processing technology was applied to obtain the transmission value of the light beam passing through the Al dust cloud at different locations within a vessel. The images obtained by the high‐speed camera indicated that the dispersion process had three stages, that is, a fast injection stage, diffusion stage, and stabilization stage. By examining the transmission‐time histories at 13 different locations in the chamber and at various Al concentrations (from 100 to 800 g/m 3 ), the decay behavior of transmission under different concentrations was obtained, and the decay time fluctuated from 44 to 68 ms. By comparing the deviation of transmission at different locations and for various concentrations in the stabilization stage, the maximum SD obtained was 8.2%, that meant the dust clouds were relatively uniform. Finally, based on the experimental results, the ignition delay time (after which the powder/air mixture is considered homogeneous) corresponding to different dust concentrations should be different to ensure the accuracy of explosion characteristics test.